A Multiband Slot Antenna loaded with Stubs for WLAN/WiMAX/Satellite TV Applications - Khan, I.; Ali, T.; Devanagavi, G. D.; K R, S.; Biradar, R. C (Advanced Electromagnetics, 2018)
A compact planar multiband antenna operating at 2.65 (lower WiMAX)/5.20 (WLAN)/6.75/7.30 GHz (Satellite TV) is presented. The antenna consists of circular radiator in which a rectangular slot is etched out. Also, the circular radiator is loaded with a rectangular and two hook-shaped stubs to achieve multiband operations. The impedance matching at these bands is achieved by using two small square stubs placed inside the hook-shaped stubs. The antenna has an electrical dimension of 0.17λl x 0.17λl x 0.01λl at the lower frequency of 2.65 GHz. The antenna has S11<-10dB bandwidth of 3% (2.6-2.68GHz), 2.3% (5.12-5.24GHz), 1.2% (6.68-6.76GHz) and 1.37% (7.26-7.36GHz) in simulation and about 6.25% (2.48-2.64GHz), 2.24% (5.3-5.42GHz), 1.15% (6.92-7.00GHz) and 1.1% (8.04-8.12GHz) under measurement. The entire simulation analysis of the antenna is carried out using HFSS v.13.0.